Changes in Functional Status After Aquatic Exercise in Adults with Type 2 Diabetes and Arthritis: A Pilot Study. Issue 1 (2nd January 2019) - Johnson, Steven T.; Mundt, Clark; Qiu, Weiyu; Boulé, Normand; Jorgensen, Lene; Bell, Gordon; Vallance, Jeff K.; Taylor, Lorian M.; Eshghi, Saeed R.; Johnson, Jeffrey A.
ABSTRACT: Background : Arthritis is highly prevalent among older adults with type 2 diabetes mellitus (T2DM) and presents a barrier to participating in regular land-based physical activity. Aim : To examine the effects of a 12-week community-based aquatic exercise program for overweight older adults (≥55 years of age) with T2DM and lower body arthritis. Methods : For this quasi-experimental study, participants completed an exercise specialist-led program consisting of 60-min, twice/week, of aquatic activities at intensities that increased at 4-week increments from 40% to 65% of heart rate reserve for a total of 12 weeks. Clinical and functional measures were completed at baseline and after 12 weeks. Results : Thirty participants completed baseline measures. Overall, half were female, mean (standard deviation = SD ) age 67.7 (7.0) years, A1c = 6.7 (1.3)%, BMI = 35.9 (8.6) kg/m 2, average daily steps = 4207 (5504). Actual mean heart rate responses during aquatic exercise sessions were at 85%, 90%, and 85% of what was prescribed at weeks 4, 8, and 12, respectively. After 12 weeks, improvements were found for 6-min walking distance (+16.6, SD 43.4 m; p = .05), sit-to-stand repetitions (+1.0, SD 2.0; p = .01), and BMI (−0.2, SD 0.6 kg/m 2 ; p = .04) Conclusion : This pilot study showed that an aquatic program produced functional improvements among overweight older adults with T2DM and arthritis.